The contributions of egocentric and allocentric reference frames in haptic spatial tasks - Kappers, Astrid M.L. (Acta psychologica, 2004)
The influence of egocentric and allocentric reference frames on performance in haptic spatial tasks, was tested in three conditions. Blindfolded subjects had to make two bars haptically parallel, perpendicular or mirrored in the midsagittal plane. The hypothesis is that the contributions of egocentric and allocentric reference frames are combined, resulting in settings that lie in between the allo-representation and the ego-representation. This leads to different predictions for the outcome of different conditions. All findings were consistent with the hypothesis. In addition, for subjects with large deviations a reversal of the oblique effect was found once again, which provides extra support for the hypothesis.